Subnational favoritism in development grant allocations - Empirical evidence from decentralized Indonesia - Gerrit J. Gonschorek (University of Freiburg, Department of International Economic Policy (iep), 2020)
Are public grant allocations biased toward the birth districts of governors, and if so, what explains this favoritism? The allocation of budget authority to local government officials is a common trend around the developing world but is often criticized for transferring favoritism from the center to lower government levels. To limit the risk of such grant manipulations in fiscally decentralized countries, it is crucial to analyze the influence of such informal ties at the subnational level. Using a unique panel data set of 410 Indonesian districts for the period 2005-2013, I exploit the discretionary nature of a government grant and a large amount of asynchronous local direct elections to investigate if the origin of the provincial governor determines fund allocations to the district level. I show that birth districts of incumbent governors receive significantly larger shares of discretionary grants compared with the other districts within a province. Local favoritism is driven by governors with a political history in the mayor's office of their birth district and limited by local electoral accountability. Classical pork- barrel politics, however, as reelection motives or formal political party ties to the district administration, do not explain local favoritism. The allocations of formula-based transfers, which limit the discretionary power of a governor, are not affected by local favoritism. These results illustrate the importance of non-discretionary institutional grant design and local democratization reforms in the context of Indonesia's political system. The country is a young democracy characterized by low ideological cleavages, little party loyalty, and the prevalence of money politics in its highly decentralized fiscal system. These features are not unique to Indonesia and characterize a number of developing countries; however, and they are in sharp contrast to established democracies for which subnational favoritism has been analyzed.
Keywords: 330; Fiscal Decentralization; Subnational Favoritism; Discretionary Grants; Local Elections; Indonesia